Penerapan Metode MABAC Untuk Mendukung Pengambilan Keputusan Pemilihan Kepala Cabang Pada PT. Cefa Indonesia Sejahtera Lestari - Noveriang Ndruru; Mesran Mesran; Fince Tinus Waruwu; Dito Putro Utomo (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
The election of the branch head is prioritized to support the performance process and the continuous control process so in the election must have criteria that are able to give the right decision the criteria in question are education, experience, absenteeism and responsibility. Election of branch heads at PT. Cefa Indonesia Prosperous Lestari is carried out by receiving files from the company secretary's report, then an assessment is made based on predetermined criteria. The author chose the MABAC method (MULTI ATTRIBUTIVE BORDER APPROXIMATION AREA COMPARISON). used to analyze different alternatives and estimate alternatives according to their level of ultility where the values of the attributes are expressed in intervals to increase efficiency and improve accuracy in the decision making process.